Deformation Behaviour of a High Carbon Co–Cr–Mo Medium-Entropy Alloy via Thermal Oxidation - Rosdi, Daud; Mas Ayu, Hassan; R., Norizah; A. K., Nasution (Springer Singapore, 2023)
Thermal oxidation is widely used in substrate surface modification before applying bioceramic coating to enhance implant resistant against corrosion and biocompatibility. In this work, mechanical and microstructural characteristics of a medium-entropy alloy Co61.9Cr29.6Mo6.5C0.24 (in wt.%) was thermally oxidize under controlled furnace atmosphere, at 450 °C, 650 °C, 850 °C, 1050 °C and 1250 °C for 3 h. It has been demonstrated that by oxidizing high carbon Co–Cr–Mo alloy can create a reasonably thick, stable and hard Cr2O3 layer on the substrate at 1050 °C. The exchange of substrate colour from silver to brownish and lastly dark green of oxide layer was observed and is evident from the variations of the surface morphology which is also a cause response to the increment of temperature. Within the interval of extremely high temperature considered (1250 °C), the alloy exhibits several unusual features, such as presence of massive porosity with clumpy blended of distinct composition of oxide layer like CoCr2O4 and Co0.8Cr0.2. The results also demonstrate that Cr2O3 layer recede in thickness as the temperature reaches 1250 °C and experienced oxide layer spalling due to bounteous chemosorption of O2 atoms react with dominant elements like cobalt and chromium in the substrate.